Elevated Soluble CD163 in Gestational Diabetes Mellitus: Secretion from Human Placenta and Adipose Tissue - Bari, Muhammad Furqan (Public Library of Science, 2014)
Recently soluble CD163 (sCD163), a cleaved form of the macrophage receptor CD163, was identified as a macrophage-specific risk-predictor for developing Type 2 Diabetes. Here, we investigate circulating levels of sCD163 in gestational diabetes mellitus (GDM). Furthermore, given the role of the placenta in the pathogenesis of GDM, we assessed placental contribution to sCD163 secretion. Paired maternal (venous) and umbilical vein blood samples from GDM (n = 18) and Body Mass Index (BMI) matched control women (n = 20) delivered by caesarean section at 39–40 week gestation were assessed for circulating levels of sCD163, Tumour necrosis factor alpha (TNF-α) and Interleukin 6 (IL-6). Media from explant culture of maternal subcutaneous fat and corresponding placental tissues were assayed for these same molecules. CD163 positive cell numbers were determined in placental and adipose tissues of GDM and control women. We found significantly elevated circulating sCD163 levels in GDM mothers (688.4±46.9 ng/ml vs. 505.6±38.6 ng/ml) and their offspring (418.2±26.6 ng/ml vs. 336.3±24.4 ng/ml [p<0.05 for both]) as compared to controls, together with elevated circulating TNF-α and IL-6 levels. Moreover, both GDM placentae (268.1±10.8 ng/ml/mg vs. 187.6±20.6 ng/ml/mg) and adipose explants (41.1±2.7 ng/ml/mg vs. 26.6±2.4 ng/ml/mg) released significantly more sCD163 than controls. Lastly, significantly more CD163 positive cells were observed in GDM placentae (25.7±1.1 vs. 22.1±1.2) and adipose tissue (19.1±1.1 vs 12.7±0.9) compared to controls. We describe elevated sCD163 levels in GDM and identify human placenta as a novel source of sCD163 suggesting that placental tissues might contribute to the increased levels of circulating sCD163 in GDM pregnancies.